Building and Sustaining Buyer–Seller Relationships in Mature Industrial Markets - Narayandas, Das; Rangan, V. Kasturi (Journal of Marketing, 2004)
Empirical research in relationship management has tended to take a snapshot of a relationship at a given time and attempt to project its trajectory, despite agreement among researchers that a longitudinal perspective focused on process models advances the implications for practice. The authors use a field investigative approach to study, over time, the evolution of three industrial buyer–seller relationships in mature industrial markets. The relationships are characterized by various degrees of initial asymmetry and have evolved in dramatically different ways over time. Their findings suggest that weaker firms can structure and thrive in long-term relationships with powerful partners because initial asymmetries are subsequently redressed through the development of high levels of interpersonal trust across the dyad, which in turn leads to increased levels of interorganizational commitment.